Correlation between Fibrinogen Level with Middle Cerebral Artery Pulsatility Index in Acute Ischemic Stroke - Rika Ainun Tikha, -
Abstract Background: High levels of fibrinogen will increase the blood viscosity. Pulsatility index parameter in transcranial doppler can measure blood vessel resistance which influence by cerebral blood flow velocity and blood viscosity. This study has aim to find correlation between fibrinogen with PI in acute thrombotic stroke patient. Method: A cross sectional design was used in this study. The samples were patient with acute ischemic stroke in neurological ward Dr. Soetomo Hospital Surabaya from January 2019 to December 2020. Fibrinogen level was measured using clauss method. PI was calculated by peak systolic velocity, end diastolic velocity and mean vessel velocity, which were measured in middle cerebral artery. Result: This study involved 32 samples consisted 22 males and 10 females. Mean age of subjects was 55.37 ± 10.55. The mean fibrinogen level is 356.95 ± 139.57. Mean MCA PI is 1.03 ±0.34. There is positive correlation with weak correlation strength between fibrinogen level with MCA PI in acute thrombotic stroke patients and statistically significant (p=0.024, r=0.398). Conclusion: There is a positive correlation between fibrinogen level with PI MCA in acute thrombotic stroke.